INFORMATION SECURITY FROM LEAKS TECHNICAL CHANNELS - Конахович, Г.Ф.; Назаренко, Є.Л.; Свириденко, В.М. (Science-based technologies, 2009)
With development of engineering and information technologies, for last years rates of development of technical devices for the non-authorized mastering by the information considerably have increased. For today there is a set of means of interception of the information with the help of different devices: radiomicrophones, device of in-terception of the telephone messages, and it is a lot of others. But also there are many means of protection of the information: mufflers of dictophones, blockers of cellular connection, devices of protection of the electric sys-tem, generators of noise.